2014
DOI: 10.1161/hypertensionaha.113.03058
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Level of Cord Blood Circulating Endothelial Colony–Forming Cells in Preeclampsia

Abstract: Preeclampsia is a pregnancy-related disorder associated with increased cardiovascular risk for the offspring. Endothelial colony-forming cells (ECFCs) are a subset of circulating endothelial progenitor cells that participate in the formation of vasculature during development. However, the effect of preeclampsia on fetal levels of ECFCs is largely unknown. In this study, we sought to determine whether cord blood ECFC abundance and function are altered in preeclampsia. We conducted a prospective cohort study tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 26 publications
5
55
1
Order By: Relevance
“…7 This finding was consistent after adjustment of most obstetric factors, suggesting that level of ECFCs was an independent factor in preeclampsia. 7 Moreover, recent studies have shown many important confounding factors on circulating levels of ECFCs, including body mass index and gestational age. 8 Furthermore, Yoder and colleagues 9 demonstrated that early endothelial progenitor cells that generate endothelial cell colony-forming units are hematopoietic in origin, fail to form perfused vessels in vivo, and are clonally distinct from ECFCs; thus, in addition to variations in the number of AC133þ/KDRþ/CD34 þ endothelial progenitor cells, which are distinguished from ECFCs, it remains unclear whether preeclampsia altered baseline levels in the peripheral blood ECFCs.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…7 This finding was consistent after adjustment of most obstetric factors, suggesting that level of ECFCs was an independent factor in preeclampsia. 7 Moreover, recent studies have shown many important confounding factors on circulating levels of ECFCs, including body mass index and gestational age. 8 Furthermore, Yoder and colleagues 9 demonstrated that early endothelial progenitor cells that generate endothelial cell colony-forming units are hematopoietic in origin, fail to form perfused vessels in vivo, and are clonally distinct from ECFCs; thus, in addition to variations in the number of AC133þ/KDRþ/CD34 þ endothelial progenitor cells, which are distinguished from ECFCs, it remains unclear whether preeclampsia altered baseline levels in the peripheral blood ECFCs.…”
supporting
confidence: 62%
“…By contrast, the ECFC level in preeclampsia was statistically lower than in the control, with a median abundance of 1 colony per 10 mL of cord blood and a 25 th to 75 th interquartile range of 0 to 4 colonies per 10 mL of cord blood. 7 In addition, a significant portion of the women with preeclampsia in their study had no measurable ECFCs. 7 This finding was consistent after adjustment of most obstetric factors, suggesting that level of ECFCs was an independent factor in preeclampsia.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…VEGF-NO signaling is impaired in circulating ECFCs isolated from the cord blood of preterm infants [91]. Recently ECFCs were shown to be decreased in cord blood of mothers with preeclampsia suggesting that impaired progenitor cell-mediated vasculogenesis is a mechanism through which the infant is affected by this maternal complication of pregnancy [92, 93]. ECFCs may also contribute to development of the placental vasculature and maternal vascular underperfusion (MVU) in the placenta is associated with BPD risk [94].…”
Section: Introductionmentioning
confidence: 99%